Way Down in the Hole: Adaptation to Long-Term Water Loss in Rural India - Blakeslee, David, Ram, Fishman, and Veena, Srinivasan (American Economic Review)
Worsening environmental conditions threaten to undermine progress in reducing rural poverty. Little is known, however, about the prospects for farmer adaptations to mitigate this threat, in particular through opportunities for income diversification presented by recent non-agricultural growth. We study the effects of increasing water scarcity in India using quasi-random, geologically determined differences in access to groundwater. The drying up of wells results in a precipitous and persistent decline in farm income and wealth, with little evidence of agricultural adaptation. However, labor reallocation to off-farm employment appears successful in maintaining overall income, particularly in locations with a more developed manufacturing sector. - Reproduced
Keywords: Water resources - India; Economic Development - India